Managerial incentives and management forecast precision - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2011)
Despite managers’ great discretion in determining management forecast characteristics, little is known about how managerial incentives affect these characteristics. In this paper we examine whether managers strategically choose the precision, or the specificity, of their earnings forecasts for self-serving purposes. Built on the finding that the market reaction to vague management forecasts is weaker than that to precise forecasts, we find that for management forecasts disclosed before insider sales, good news are more precise and bad news are less precise than other management forecasts. The opposite applies to management forecasts disclosed before insider purchases. These results are consistent with managers choosing the precision of their earnings forecasts to increase stock prices before insider sales and to decrease stock prices before insider purchases. Additional analyses indicate that the impact of managerial incentives on forecast precision is less pronounced when institutional ownership is high or when disclosure risk is high, and is more pronounced when it is more difficult for investors to assess the precision of managers’ information.